Superstitions, Religious Identity, and COVID-19 Conspiracy Beliefs in Secularized Czechia - Zawistowska, Alicja (Journal of religion in Europe, 2025)
The paper explores how individuals’ religious identity—categorized as non-religious, religious but not affiliated, and religiously affiliated with traditional churches—influences COVID-19 conspiracy beliefs in Czechia. Based on an online sample of more than 7,800 Czech participants, our findings indicate that religiously affiliated individuals were less likely to endorse COVID-19 conspiracy beliefs compared to religious but not affiliated individuals. However, after accounting for individuals’ superstitious beliefs, the differences in COVID-19 conspiracy beliefs between the three categories became negligible. Additionally, we found that public practices negatively affected COVID-19 conspiracy beliefs among individuals affiliated with traditional churches.